2015
DOI: 10.1038/nature14286
|View full text |Cite
|
Sign up to set email alerts
|

Two insulin receptors determine alternative wing morphs in planthoppers

Abstract: Wing polyphenism is an evolutionarily successful feature found in a wide range of insects. Long-winged morphs can fly, which allows them to escape adverse habitats and track changing resources, whereas short-winged morphs are flightless, but usually possess higher fecundity than the winged morphs. Studies on aphids, crickets and planthoppers have revealed that alternative wing morphs develop in response to various environmental cues, and that the response to these cues may be mediated by developmental hormones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
449
3
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 383 publications
(468 citation statements)
references
References 36 publications
15
449
3
1
Order By: Relevance
“…IIS may also be responsible for the reduction in eye size and wing size observed in small D. melanogaster individuals (Tang et al, 2011). More extreme variation in tissue growth has been observed in other insects, where it is associated with IIS, but also JH, ecdysone and even the hedgehog signaling pathway (Lobbia et al, 2003;Emlen et al, 2012;Gotoh et al, 2014;Niitsu et al, 2014;Kijimoto and Moczek, 2016;Xu et al, 2015; see also the excellent discussion in Zinna et al, 2016). Any or all of these factors (and others yet to be discovered) are candidate caste differentiation factors in ants.…”
Section: Caste Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…IIS may also be responsible for the reduction in eye size and wing size observed in small D. melanogaster individuals (Tang et al, 2011). More extreme variation in tissue growth has been observed in other insects, where it is associated with IIS, but also JH, ecdysone and even the hedgehog signaling pathway (Lobbia et al, 2003;Emlen et al, 2012;Gotoh et al, 2014;Niitsu et al, 2014;Kijimoto and Moczek, 2016;Xu et al, 2015; see also the excellent discussion in Zinna et al, 2016). Any or all of these factors (and others yet to be discovered) are candidate caste differentiation factors in ants.…”
Section: Caste Differentiationmentioning
confidence: 99%
“…Here, we attempt to unify the literature on ant caste development and evolution with a single theoretical framework, drawing on recent advances in evolutionary developmental biology (Carroll et al, 2001;West-Eberhard, 2003;Hartfelder and Emlen, 2012;Bopp et al, 2014;Wagner, 2014;Londe et al, 2015;Xu et al, 2015). We propose that ants possess a developmental spectrum of phenotypes, with increasing body size associated with increasingly queen-like traits (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…NlInR1 and NlInR2 closely resemble each other as well as their Drosophila counterpart with respect to amino acid identity and domain architecture [50]. Surprisingly, NlInR1 and NlInR2 play fully opposite roles in wing-morph determination in the BPH.…”
Section: Environmental Factors Influencing Wing Dimorphism In the Bromentioning
confidence: 84%
“…These breakthrough findings suggest that the BPH employs the same suit of genes to generate different wing morphs in different environments by alternating their expressional levels. Further, functional studies on insulin receptors from additional two planthopper species, L. striatellus and S. furcifera, indicated that the planthopper family might share a common regulatory mechanism underlying wing dimorphism [50]. Thus, we refer to the wing-morph plasticity in planthoppers as wing polyphenism instead of wing polymorphism, as alternative wing morphs are caused by redeployment of the existing developmental pathways, but are not genetically determined.…”
Section: Environmental Factors Influencing Wing Dimorphism In the Bromentioning
confidence: 99%
See 1 more Smart Citation